Effect of diagnostic threshold on the validity and reliability of epidemiological caries diagnosis using the Dundee Selectable Threshold Method for caries diagnosis (DSTM) - Fyffe HE, Deery C, Nugent ZJ, Nuttall NM, Pitts NB: (Blackwell Synergy, 2000)
To develop a method for recording dental caries at the D1 (enamel and dentine) diagnostic threshold (without loss of D3 information) and assess its reliability, ‘benchmark’ validity and potential effects on reported caries prevalence and needs assessment. Methods: Multi-examiner training, calibration and validation trial. Two groups of 10 dental examiners were trained to diagnose dental caries at the D1 (enamel and dentine) diagnostic threshold under the conditions of a caries prevalence survey, prior to a calibration trial being undertaken. Results: Where ‘experienced examiners’ were trained to examine at the D1 (enamel and dentine) diagnostic threshold, under the conditions of a cross-sectional epidemiological survey, there was no significant deterioration in inter-examiner agreement on the assessment of teeth and a significant difference in one of two comparisons on the assessment of surfaces using the kappa statistic.